AN ANALYSIS ON THE STUDENTS’ INDIRECT LEARNING STRATEGIES IN WRITING SKILL - Yusri .; Tri Setiani (Jurnal Didascein Bahasa, 2018)
The problem of this study was “what are the indirect learning strategies in writing skill applied by the eleventh grade students of SMAN 12 Palembang?” The objective of this study was to find out the indirect learning strategies in writing skill applied by the eleventh grade students of State Senior High School 12 Palembang. This study used qualitative descriptive method. The population of this study was 232 of the eleventh grade students of State Senior High School 12 Palembang in the academic year of 2016 / 2017. This study used purposive sampling technique. The data were collected through the SILL questionnaire and documentation. Based on the study, it showed that eventhough there was no learning strategy applied by the students in the high use, but according to the average use of the strategy, metacognitive strategies (Mean = 3.28) became the most frequently strategies applied by the students, then, followed by affective strategies (Mean = 2.65), and the last was social strategies (Mean = 2.46). In conclusion, all the indirect learning strategies in writing skill that are metacognitive, affective, and social strategies were applied by the eleventh grade students of State Senior High School 12 Palembang. Keywords: Analysis, Indirect Learning Strategies, Writing Skill.